Analisis Penyimpanan Hujan DAS Akibat Pengurangan Jumlah Stasiun Hujan DAS Oyo - DEARLY A. Y., Abang Muhammad ([Yogyakarta] : Universitas Gadjah Mada, 2014)
An advanced hydrolical analysis may require rainfall data. Therefore arainfall data that can represents total precipitation over a catchment area is needed because it will directly affect analytical result. The more rain gauge provided inside a catchment area will represent precipitation of that areabetter than if less rain gauge provided. It is because those rain gauges will cover most area of a catchment area much better. On the other side more rain gauge may cause more problemnotablythe operational cost. An high operational cost might cause some rain gauge to be taken off of cathment area due to lack of operational budget. Indeed this removed rain gauge will cause deviated catchment rainfall over the actual rain gauge system. The deviation of catchment rainfall may differ on one removed rain gauge to another. This research conducted to find which order of rain gauge on Oyo basin that will give the most accurate data by comparing the catcment rainfall of actual rain gauge system with catchment rainfall of removed rain gauge(s). Result of this research shows that rainfall gauge order that gives the best result for 6 rain gauge, 5 rain gauge, 4 rain gauge, 3 rain gauge, 2 rain gauge and 1 rain gauge respectively are Terong, Panggang, Gedangan, Ngawen, KedungKeris, Wonogomo; Terong, Panggang, Gedangan, Ngawen, Wonogomo; Panggang, Gedangan, Ngawen, Wonogomo; Terong, Gedangan, Ngawen; Ngawen, Kedung Keris;and Kedung Keris Keywords : Catchment Area Rainfall, Deviation, Oyo basin